A Study on Generalized Multivariable Mittag-Leffler Function via Generalized Fractional Calculus Operators. (1st August 2019) - Suthar, D. L.; Andualem, Mitku; Debalkie, Belete
Abstract : We study some properties of generalized multivariable Mittag-Leffler function. Also we establish two theorems, which give the images of this function under the generalized fractional integral operators involving Fox's H-function as kernel. Relating affirmations in terms of Saigo, Erd é lyi-Kober, Riemann-Liouville, and Weyl type of fractional integrals are also presented. Some known special cases have also been mentioned in the concluding section.